Treatment of pyogenic granuloma with copper vapor laser radiation - Igor V. Ponomarev; Ludmila D. Shakina; Sergey B. Topchiy; Svetlana V. Klyuchareva; Alexandra E. Pushkareva (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. Pyogenic granuloma (PG) or lobular capillary hemangioma, ICD10 code: L98.0. appears as a single bright red or violet papule up to 20 mm in size, on the face, fingers, skull surface, arms, and intergluteal fold, as well as on the oral mucous membranes. Surgical removal of facial PG is not always possible due to insufficient thickness of the dermis. Treatment of PG with a pulsed dye laser (PDL) or neodymium laser (Nd:YAG) can achieve a noticeable elimination of the lesion but is reported to be accompanied by such side effects as purpura or scarring. It determines the feasibility of introducing into clinical practice the methods of laser treatment of PG using the radiation of a copper vapor laser (CVL) with a wavelength of 578 nm, which effectively absorbed by the blood. Aim. The assessment of the clinical efficacy and safety of the CVL treating PG. Methods. 26 adult patients with PG in various parts of the face, including the lips, limbs, and trunk, were included in this study. PG treatment was carried out in one session with CVL (Yakhroma-Med, FIAN) at an average power of 0.71.0 W, at a wavelength of 578 nm, exposure time 0.20.3 s. The diameter of the light spot is 1 mm. Results. Immediately after the single laser treatment, the PG involved area became grey. In 710 days, the irradiated area was utterly similar to the adjacent intact skin. No postoperative bleeding or infection was noted. Side effects included mild skin atrophy. During the follow-up observation for five years, no side effects were found. Conclusion. The high efficiency of PG elimination using CVL in the absence of pronounced side effects allows suggesting this method for introducing into dermatologists and cosmetologists' clinical practice as a highly effective and inexpensive method of treatment.